if cosec tita + cot tita = x then find the value of cosec tita - cot tita
Answers
Answered by
3
here is my answer hope u will undrstnd
Attachments:
![](https://hi-static.z-dn.net/files/daf/7aca5f356b4fef899c52a03a4efb462a.jpg)
Answered by
2
Given Equation is cosec theta + cot theta = x ---- (1)
We know that cosec^2 theta = 1 + cot^2 theta
Then cosec^2 theta - cot^2 theta = 1.
We know that (a^2 - b^2) = (a + b)(a - b)
Then (cosec^2 theta - cot^2 theta) = 1 :
(cosec theta + cot theta)(cosec theta - cot theta) = 1
(x)(cosec theta - cot theta) = 1
(cosec theta - cot theta) = 1/x.
Hope this helps!
We know that cosec^2 theta = 1 + cot^2 theta
Then cosec^2 theta - cot^2 theta = 1.
We know that (a^2 - b^2) = (a + b)(a - b)
Then (cosec^2 theta - cot^2 theta) = 1 :
(cosec theta + cot theta)(cosec theta - cot theta) = 1
(x)(cosec theta - cot theta) = 1
(cosec theta - cot theta) = 1/x.
Hope this helps!
Similar questions